Sustainability of dialecticity in the regions of Lithuania: the perspective of the EMIC narrative constructor - Aliūkaitė, Daiva (Lietuvių kalba, 2020)
The paper expands on the problem of sustainability of dialecticity, i.e. the conditions and the potential of the dialect codes in the regions of Lithuania based on the data of the project “Distribution of Regional Variants and Quasistandard Language at the Beginning of the 21st Century: Perceptual Approach (Perceptual Categorisation of Variants)”. It aims to reveal whether and to what extent the narrative of an ordinary member of a language community allows to approach regional dialecticity via the dimension of (non)sustainability of dialecticity.The empirical basis for the analytical discourse developed in the paper was constructed from the data revealing the language attitudes of 910 young persons from 21 regional points (which in the etic narratives were estimated as includable into the zone of the already formed (or forming) variant on the basis of the traditional dialect), fixed by applying the instrumentarium worked out in perceptual dialectology (PD).Having generalised the data of language self-observation and acknowledgement of dialecticity in the micro-/macro-environment, it might be claimed that, in the region of Lowland dialecticity, the areas of the sustainable dialecticity dominate: here, no less than 2/3 of the community might be estimated as having the potential to choose and realise the dialect code.The PD research including the young Highland people, which was based on the comparative analysis of the data, concerning the application of the language behaviour of young people and their a priori attitudes toward the spread of the dialect code, led to the observation that the following ab intus estimations of the dialect codes have been constructed: I am more tolerant toward it; I show less attempt at self-identification.It should be stressed that, in the regions of Highland dialecticity, not merely the areas of the sustainable dialecticity have been fixed, where the communal members firmly positioned their identity as active (im)permanent representatives of the dialect code. The emic narratives reconstructed from the PD research data allowed to distinguish the areas of the relatively sustainable dialecticity, where only around 1/2 of communal members might be identified as the active (im)permanent representatives of the dialect code, and the areas of the unsustainable dialecticity where only 1/3 and less of the communal members were apt to recognise their dialect identification.The holistic estimation of both the Lowland and the Highland dialecticity, based on the reconstructed fragments of the emic narratives revealing the tendencies of code adjustment, led to the conclusion that Lowland dialecticity should be claimed as more sustainable.It should be maintained that the concluding remarks are based on the reconstruction of the emic narratives of the group of recipient participants who represent one age category. Therefore, to achieve a more accurate (non)sustainability discourse in dialectology, further steps are required, e.g. the PD research should include the recipients of various age groups; the results obtained in the PD analysis should be compared with the data of direct observation, etc.
Keywords: sustainability of dialecticity; emic narrative; an ordinary member of the language community; perceptual dialectology